Optimization of 3D-Visualization of Micro-Anatomical Structures of the Human Inner Ear in Osmium Tetroxide Contrast Enhanced Micro-CT Scans - van den Boogert, Thomas; van Hoof, Marc; Handschuh, Stephan; Glueckert, Rudolf; Guinand, Nils; Guyot, Jean-Philippe; Kingma, Herman; Perez-Fornos, Angelica; Seppen, Bart; Johnson Chacko, Lejo; Schrott-Fischer, Anneliese; van de Berg, Raymond (Frontiers in Neuroanatomy, 2018)
Abstract Introduction. Knowledge of the neuro-anatomical architecture of the inner ear contributes to the improvement and development of cochlear and vestibular implants. The present knowledge is mainly based on two-dimensional images (histology) or derived models that simplify the complexity of this architecture. This study investigated the feasibility of visualising relevant neuro-anatomical structures of the inner ear in a dynamic three-dimensional reproduction, using a combination of staining, micro-CT imaging and an image processing algorithm. Methods. Four fresh cadaveric temporal bones were postfixed with osmium tetroxide (OsO4) and decalcified with EDTA. Micro-CT was used for scanning at 10 micrometres (4 scans) and 5.5 micrometres (1 scan) voxel resolution. A new image processing algorithm was developed and the scans were visualised in open source software. Results. OsO4 enhanced the contrast in all scans and the visualisation was substantially improved by the image processing algorithm. The three-dimensional renderings provided detailed visualisation of the whole inner ear. Details were visible up to the size of individual neurons, nerve crossings and the specific neuro-anatomical structures such as the tunnel of Corti. Conclusion. The combination of OsO4, micro-CT and the proposed image processing algorithm provides an accurate and detailed visualisation of the three-dimensional micro-anatomy of the human inner ear.